Analisa Kinerja Reaktor Pirolysis Tanpa Menggunakan Bahan Bakar dalam Menghasilkan Bio-Arang Dan Asap Cair - Rajabiah, Nurlaila; Ridhuan, Kemas; Mafrudin, Mafrudin; Saputra, Nugroho Adi (TURBO [Tulisan Riset Berbasis Online], 2023)
The combustion process of pyrolysis needs fuel as a heat source. The pyrolysis process can be performed without fuel, which reduces costs and increases process efficiency. The quantity of charcoal and liquid smoke, as well as the duration of the pyrolysis process, are the main objectives of this study. The research technique that uses rubber wood as a raw material and pyrolysis combustion in a reactor devoid of fuel or heat source. According to study findings, the yield of charcoal products was 33.0%, while that of liquid smoke was 7.3%. The pyrolysis combustion process lasted for 270 minutes, during which time the reactor's maximum raw material flame combustion temperature reached 447C. The results of the pyrolysis of charcoal have the following characteristics: 9.19% water content, 4.52% ash content, and 7475.87 cal/gr heat content. Burning pyrolysis without fuel can save three times as much biomass as burning pyrolysis with fuel.Keywords: Pyrolysis, Combustion, Biomass, Charcoal, Liquid smoke.